Conceptualizing, defining, and modelling supply chain management : an objective oriented approach. - Alkebaisi, Hussain K (Cranfield University, 2022)
Although it has been more than three decades since the term Supply Chain Management (SCM) was first introduced, there are still divergent views and different interpretations amongst scholars and practitioners about its meaning. The literature lacks consensus on a precise definition of SCM and presents a plethora of different perspectives. A unified conceptual or theoretical model has not yet been acknowledged, and the existing frameworks lack the call for a holistic model that encompasses the essence of the concept. With this disagreement on what SCM is, there are repeated calls to achieve consensus on a unified definition, a unified understanding, a unified conceptual model, and a unified framework of SCM. The argument in the literature is that achieving consensus among scholars and practitioners will improve research and practice and the SCM discipline. The literature revealed that the prevalent and the most recommended approach of conceptualising SCM is the process orientation. However, there is no evidence in the literature that an objective-oriented approach was investigated in resolving those theoretical issues, and neither has a Grounded Theory research method been applied to that end.Through an objective-orientated approach and applying the grounded theory method, it is found that the majority of the theory behind SCM is about managing business activities and achieving business goals through the communication, cooperation, collaboration, and integration within and across firms in a supply chain or network. The proposed name of the identified theory is ‘Business Relations Management Theory.’ The theory states that individuals, organisations, societies and nations achieve better performance and outcomes through communication, cooperation, collaboration, and integration. A literature-based thematic analysis showed that SCM is being used as a synonym for Supply Management, Business Relations Management (BRM), or a combination of both. Also, an assessment survey that included more than 200 managers and employees from different countries showed unclear or limited understanding of the identified theory and perspective of BRM. Accordingly, this research presents the theory and perspective of BRM and asserts that the term Supply Chain Management (SCM) should be replaced with Business Relations Management (BRM). SCM, as a term, limits the benefits of communication, cooperation, collaboration, and integration to a chain or network of firms and enterprises within the production sector. In contrast, the Business Relations Management (BRM) concept generalises the benefits to all sectors and all stakeholders, including the final customers, consumers, and services recipients. In addition, universities or business schools are advised to replace SCM with ‘Supply Management’ or another name that combines supply and demand management fields. A Feedback survey included a group of managers and employees from different sectors in Bahrain showed a high level of satisfaction and acceptance of the outcomes of this research, the researcher’s argument, and recommendations. The feedback survey outcomes led to the conclusion that the objective orientation was an effective approach to conceptualise SCM, and there is a probability of higher acceptance of the outcomes of this research and, consequently, achieving consensus among academics and practitioners.
© Cranfield University 2022. All rights reserved. No part of this publication may be reproduced without the written permission of the copyright owner
Keywords: Supply Chain Management; Business Relations Management; Human Purposeful Action Theory; Grounded Theory